Comparative analysis of organic and conventional farm sustainability in peri-urban zones of Rabat, Morocco: insights and perspectives - Fatiha Hakimi; Sara Sehli; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd_Allah (Cogent Food & Agriculture)
Agriculture in peri-urban Rabat faces challenges such as rising input costs, an aging workforce, and labor retention issues, threatening farm sustainability. This study compares the sustainability of organic and conventional farms using the IDEA method, adapted to the local context. Assessing 30 farms (15 organic, 15 conventional) across agro-environmental, socio-territorial, and economic dimensions, the study employs tailored assessment criteria and an adapted scoring system, creating a detailed grid with 18 indicators spanning nine components. Data analysis and visualization were carried out using statistical methods and an Excel macro. Findings reveal that organic farms excel in agro-environmental sustainability, benefiting from biodiversity and eco-friendly practices. They also demonstrate long-term economic resilience due to short supply chains and organic labeling. In contrast, conventional farms, though more productive, face socio-territorial limitations, including weak social engagement and infrastructure, as well as economic dependence on external inputs. The study highlights organic farming’s potential to enhance sustainability in peri-urban areas through environmental stewardship and economic resilience. It suggests policy measures such as support for organic certification, infrastructure investment, and socio-territorial development programs. These insights inform strategies for improving sustainability in similar peri-urban agricultural contexts.